A descriptive study on the use of the problem-based learning strategy in the teaching of endocrinology at Angeles University Foundation College of Medicine Department of Biochemistry - Amigable-Villamor, Marivic C. (1999)
Biochemistry is a basic science subject that is introduced in the First Year of the Medical Curriculum. At the Angeles University Foundation College of Medicine, the approach used in teaching Biochemistry has always been the conventional lecture-based strategy. This method being teacher-centered has limited the participation of the learners to mere passive recipients of information. This study describes the factors involved in the development of the endocrine modules and their use in the implementation of an alternative strategy in teaching a specific topic, Endocrinology, in Biochemistry. The Problem-based Learning (PBL) approach was implemented in teaching the topic to sixty-eight (68) first year medical students at the Angeles University Foundation. Four PBL modules consisting of one community and three clinical problems, student's and facilitator's guides and a list of learning objectives for each trigger problem, were developed. These modules were used by the students and facilitators during the small group tutorial sessions. A tutorial group of 10-12 students discussed each case in tro consecutive 4-hour sessions under the supervision of one of the three facilitators from the Department of Biochemistry. A 5-point Likert scale questionnaire was employed to ascertain the perceptions of the students on the alternative method of teaching. The 15-item questionnaire had three sections that addressed the perceived influences on the learning process of the components of the PBL method namely: trigger problems, small group dynamics and facilitators. The respondents affirmed that the PBL approach motivated them to actively control the direction of their learning needs. Furthermore, the exercise encouraged the students to acquire self-learning skills. Ninety percent (90%) of the students found the PBL approach to have inspired them to take charge of their own learning. The respondents positively recognized that their expanded roles have inspired them to cooperate and be committed to the group discussion during the tutorial sessions. These findings were validated by the observations of the facilitators on student interaction during the small group tutorial sessions. The study strengthens the acceptability of the PBL as a teaching strategy and the feasibility of applying it as an alternative method of teaching Endocrinology among the First Year Medical students in a local setting.
Major project (Master in Health Professions Education)--University of the Philippines Manila
Keywords: Problem-based learning